Investigation Of The Influence Of Pressing Rolls In Extending Mechanisms On The Number Of Yarn Breaks In The Technological Process Of Yarn Spinning - S.Kh. Bobojonov; J.K. Gafurov; J.I. Oripov; B.B. Muminov (Zien Journals, 2024)
In this article, the effect of the pressing rollers in the stretching mechanisms on yarn breaks during yarn spinning is studied. The mechanical properties of the pressing rollers and how their loading affects the strength and quality of the thread have been studied. In the course of the research, practical recommendations were developed to reduce thread breaks and optimize stretching mechanisms
Keywords: Yarn spinning; stretching mechanism; pressing roller; yarn breaks